EXOSOME NANOCARRIERS: BASIC BIOLOGY, DIAGNOSIS, NOVEL AND PERSPECTIVE APPROACH IN DRUG DELIVERY SYSTEMS: A REVIEW - KUMARI, P. V. KAMALA; SRILEKHYA, KETHA; SINDHU, K. BHAVYA; RAO, Y. SRINIVASA (International Journal of Applied Pharmaceutics, 2021)
Exosomes are the extracellular vesicles surrounded by a phospholipid bilayer shed from all cell varieties and plays a significant role in the communication and Transportation of materials between the cells due to their ability to transfer the proteins and nucleic acids from One cell to the another cell. Analogous in size and performance to synthetic nanoparticles, exosomes provide several Advantages, rendering them the foremost promising candidates for targeted drug or gene delivery vehicles. This review highlights the isolation techniques and delivery potential of exosomes, and equally presents research or analysis gaps for enhancing the use of natural vesicles for delivery functions. Exosome-based drug formulations can be applied to an extensive variety of diseases such as various infectious, cardiovascular, cancer and neurodegenerative disorders. Mostly, exosomes combine the benefits of both synthetic nanocarriers and cell-mediated drug delivery systems however avoiding their limitations.